Effectiveness of STEM and Ethnoscience Integrated Digital Teaching Materials on Students' Creative Thinking Ability Phase F SMA Negeri 2 Padang - Martaliza, Leni (PILLAR OF PHYSICS EDUCATION, 2025)
This study aims to assess the effectiveness of digital teaching materials for sound waves integrated with STEM and ethnoscience approaches in improving the creative thinking skills of Phase F students at SMA Negeri 2 Padang. This study was motivated by the low creative thinking skills of students who have tended to be neglected in physics learning, especially in sound waves material. The research used a pre-experiment design with a one-group pretest-posttest design model. The sample consisted of 37 students of class XI Advanced Physics 6 who were selected by purposive sampling. The instrument used was a description test with creative thinking indicators, namely: fluency, flexibility, originality, and elaboration. The results of this study were carried out with normality test, homogeneity test, hypothesis test and N-Gain test to see the level of effectiveness. The results of the analysis showed that there was a significant increase in creative thinking skills after the application of STEM and Ethnoscience integrated sound wave digital teaching materials in learning, the hypothesis was tested using the Wilcoxon Signed-Rank Test non-parametric test with significant results <0.001 and to see the level of effectiveness of the sound wave digital teaching materials used, the N-Gain test was conducted and the average N-Gain score was 73.96% which was in the "High" category. So these findings indicate that STEM and ethnoscience integrated sound waves digital teaching materials are proven effective in improving students' creative thinking skills.